The Google Classroom for Learning Writing : Students’ Initial Perceptions - Sartika, Widya Sartika (Universitas Muhammadiyah Gresik, 2020)
This study is aimed to explore student’s initial perceptions of the application of Google Classroom to learning writing at seventh grade students. The design of this study is a survey. The researcher used a questionnaire adapted from the theoretical foundation of UTAUT2 (Unified Theory of Acceptance of Technology) to collect the data. Before conducting the research, the researcher did a preliminary study to choose the subject of the study and select 54 students from different classes that is VII-A and VII-B. The data gathered from an online questionnaire by using Google Form. The result of this study with quantitative data showed that Seventh Grade Students had a good (high) perception toward all statements of the questionnaire. Most of the student’s initial perceptions of Google Classroom application for learning writing in this study is an indicator of Performance Expectancy. It shows that (1) students find Google Classroom useful for learning English online especially writing. (2) students find Google Classroom useful which allows them to do assignment quickly. (3) using Google Classroom, students will increase their chance of learning English online for writing. The researcher recommends that this research offers several implications for the adaptation of Google Classroom in learning writing. The students’ initial perception, as evidence of students’ behavioural intentions in learning writing through learning platform and it gives beliefs to teachers in applying learning innovations refers to the usefulness of the learning platform as well as the most influential factors during implementation.